Capote - Clarke, Gerald 1937-; United Artists Corporation; Sony Pictures Classics (Firm).; A-Line Pictures; Cooper's Town Productions (Firm).; Infinity Media (Firm).; Sony Pictures Home Entertainment (Firm). (Culver City, Calif. Sony Pictures Home Entertainment, 2006)
In 1959, Truman Capote was a popular writer for The New Yorker. He learns about the horrific and senseless murder of a family of four in Holcomb, Kansas. Inspired by the story, Capote and his partner, Harper Lee, travel to the town to do research for an article. However, as Capote digs deeper into the story, he is inspired to expand the project into what would be his greatest work, "In Cold Blood." He arranges extensive interviews with the convicted killers, especially with Perry Smith. However, his feelings of compassion for Perry conflicts with his need for closure for his book which only an execution can provide. That conflict and the mixed motives for both interviewer and subject make for a troubling experience that would produce an literary account that would redefine modern non-fiction.
Library has: VDR-1645 (2 VCD's)
Based on the book by Gerald Clarke.
Special features: two audio commentary soundtracks, one with Philip Seymour Hoffman and director Bennett Miller and one with director Bennett Miller and cinematographer Adam Kimmel; two making-of featurettes; Answered prayers, a documentary on Truman Capote.
Director of photography, Adam Kimmel ; editor, Christopher Tellefsen ; music, Mychael Danna ; costume designer, Kasia Walicka-Maimone ; production designer, Jess Gonchor.
Philip Seymour Hoffman, Catherine Keener, Clifton Collins, Jr., Bruce Greenwood, Bob Balaban, Mark Pellegrino, Chris Cooper.
English and French language soundtracks with optional subtitles in English, French, Spanish, Portuguese, Chinese (Mandarin or cantonese), Korean, Thai, Bahasa Indonesia ; closed-captioned.
Keywords: Capote, Truman -- 1924-1984 -- Drama; Smith, Perry Edward -- 1928-1965 -- Drama; Clarke, Gerald -- 1937- -- Film adaptations; Authors, American -- 20th century -- Drama; Feature films; Film adaptations; Fiction films; Biographical films; Crime films; Films for the hearing impaired